[OA243] 3D Dose distribution in two clinical digital breast tomosynthesis units: A phantom study. (August 2018) - Mettivier, Giovanni; Sarno, Antonio; Di Lillo, Francesca; Masi, Marica; Sasso, Gianluigi; Bosmans, Hilde; Cockmartin, Lesley; Blisnakova, Kristina; Russo, Paolo
Abstract : Purpose: Measurements of the dose volume distribution in digital breast tomosynthesis (DBT) are lacking. They are useful for validation of Monte Carlo simulations in DBT dosimetry and also for devising models of radio-induced cancer risk in DBT exams. Due to the different scanner protocols (scan angle and spectra) the dose distribution can vary among DBT units and its determination is useful in scanner optimization and performance comparisons. We measured the dose volume distribution in breast phantoms for two DBT scanners. Methods: We employed calibrated XR-QA2 radiochromic film pieces (25 × 15 cm 2 ) placed within two layered breast phantoms: a circular homogenous PMMA phantom composed of five 1-cm thick layers with a diameter of 20 cm and a commercial BR3D CIRS mammographic phantom. Dose maps were measured at several horizontal planes in the phantom, including the entrance and exit surfaces. Two DBT scanners were employed at the University Hospital of Leuven: Hologic Selenia Dimensions and Mammomat Siemens Inspiration Prime, operated at 31 (HVL = 0.53 mmAl) and 29 kVp (HVL = 0.54 mmAl), respectively. Results: The dose distributions within the PMMA phantom did not largely depend on the scanner type. However, the measurements with the heterogeneous CIRS phantom showed larger dose differences. For the Siemens unit, the exit dose was 21% of the entrance surface dose, for both phantoms. For the Hologic unit, this value reduced to 14% and 12%, for the CIRS and the PMMA phantoms, respectively. The in-plane dose spread in PMMA, evaluated as the percentage difference from the dose in a fixed region at the chest wall, was less than a few percent for both scanners. In the case of the CIRS phantom, the maximum in-plane dose spread was 10% for the Hologic and it was reduced to less than 5% for the Siemens unit. Conclusions: 3D dose distributions were measured using two different DBT scanners. The dose spread was larger for the phantom which replicate the heterogeneous tissues distribution of the breasts. In this case, the dose spread in planes parallel to the detector is less than 10% and the entrance-to-exit dose ratio is less than 21%, for the two investigated DBT units.